Detection of Brucella Antibodies of Sheep in Al-Anbar Province by Using Some Serological Tests: Ahmed H. Al-Tae and Ekram A. Al-Samarrae - Al-Samarrae, Ekram A. (The Iraqi Journal of Veterinary Medicine, 2013)
An investigation was carried out to detect anti-Brucella antibodies of sheep in Al-Anbar province by using few serological tests; rose Bengal plate test (RBPT) and tube agglutination test (TAT). A total of 754 sheep blood samples (94 Ram and 660 Ewe) were collected randomly distributed in Al-Anbar province from unvaccinated sheep flocks with different ages. A total percentage of infected sheep depending on RBPT was 10.21% with significant differences at (P< 0.01), it was 9.69% in ewes, whereas in rams it elevated to reach 13.82%, in addition to the disease was higher seroprevalence at > 3 years (12.78%) in both gender with significant differences at (P<0.05) than lower ages. Out of 77 RBPT positive sera, 38(49.35%) were positive using TAT, there was 14 seropositive with significant differences at (P< 0.01). The study reported that brucellosis was distributed in Al-Anbar province with variable percent (3.26% to 21.27%), as well as emphasized on different epidemiological aspects.